Labor market policies and European crises - Giuseppe Bertola (IZA Journal of Labor Policy, 2014)
This paper studies theoretically and empirically why and how labor policies may reduce productivity and employment in order to stabilize labor incomes and redistribute resources. It proposes a specific stylized model where the tradeoffs facing labor policies are influenced by structural factors, inspects the empirical relevance of this mechanism in European data, and outlines the proposed theoretical perspective's implications for reform design in crisis-hit economies.
Keywords: D78; J38; 330; Uninsurable risk; Productivity; Economic integration